The waiting - Johnson, Megan, 1976- (Iowa poetry prize., 2005)
In a startling and original poetic voice, Megan Johnson in The Waiting reveals a vigilant young person who has suffered an unmentionable loss and who dismantles and reconstitutes lyric modes in a relentless search for solace. A lyric adventure of grief and search, The Waiting reinvents language from raw materials, driven by intense emotional need.